Education Of Knowledge And Basic Life Support Training For Teenage Students - Syahferi Anwar; Dudut Tanjung; Balqis Nurmauli Damanik; Marta Imelda Br Sianturi; Izmi Arisa Putri Lubis; Alisarjuni Padang (Universitas, 2024)
Individuals and groups, including the general public, are currently required to be able to provide immediate assistance when facing emergency conditions. To ensure assistance is provided according to proper procedures, it is necessary to offer training on Basic Life Support (BLS). Students of SMK Kesehatan Haji Sumatera Utara, who are teenagers with significant potential, are ideal candidates for such training. Although they are organized into a KKR Cadre Team or Youth Health Cadre group, they currently lack the necessary knowledge and need to be equipped with BLS skills. The purpose of this service is to enhance the knowledge and technological capabilities of students at SMK Kesehatan Haji Sumatera Utara regarding Basic Life Support in emergency cases. The method used includes interactive lectures, questions and answers, pre-tests, interventions, and post-tests. The results of the counseling and training showed a marked improvement in knowledge about Basic Life Support and an increase in the skills required to administer BLS. It is essential to carry out continuous counseling and socialization efforts within the school, particularly in the area of Basic Life Support